Optimalisasi Pengelolaan Sampah Organik di Desa Genteng Kulon Melalui Program Sigmaggot - Syahbana, Muhamad Ali; Siska Ayu Dewi Puspithaloka; Firdha Anugrah Cahyaningtyas; Mohammad Farezi Rachmadani; Annissa’ Maulidah Zahro; Meiviana Indah Lestari; Putri Ghaisani Fildzah; Vina Rosalina; Cahya Purnama; Ayu Diana Seviya; Sundahri (Universitas Mataram, 2025)
Genteng Kulon is one of the villages in Banyuwangi known for its potential in the agriculture, livestock, and SME (Small and Medium Enterprises) sectors. However, the main issue in the village is the volume of waste generated which reaches approximately 10 tons daily. In response to this situation, the Genteng Kulon Village Government has established a TPS 3R (Waste Management Facility for Reduce, Reuse, Recycle). One of the innovations developed is the cultivation of Black Soldier Fly (BSF) maggots, which can quickly break down organic waste in an environmentally friendly manner. Unfortunately, the program has not been running optimally due to limitations in facilities and insufficient utilization. Therefore, the students of KKN of Genteng Kulon Village, University of Jember had been explored the village's potential through entrepreneurship development from July 15, 2025, to August 19, 2025. The nutrient-rich maggots were processed into various economically valuable products such as animal feed and organic fertilizer. The program's objective was to empower the community to manage waste into economically viable business opportunities by utilizing maggots and optimizing the potential of maggots into innovative products that had not been fully developed by Genteng Kulon Village. Based on community feedback, 70% of the people in Genteng Kulon Village consider maggot farming to be “very important” and 30% consider it “quite important.” Animal feed products made from dried maggots received a positive response, with 80% of respondents considering animal feed made from dried maggots to be “more attractive” than other feeds, while 20% considered it “average.” Organic fertilizer products made from maggot waste also received a positive response, with 90% “interested in trying” and 10% “still hesitant.” These findings indicate the high potential for developing maggot farming as livestock feed and organic fertilizer in the village.